Exploring the optical properties of Vernier phase yttrium oxyfluoride thin films grown by pulsed liquid injection MOCVD. Issue 8 (6th February 2018) - Zhang, Shan-Ting; Modreanu, Mircea; Roussel, Hervé; Jiménez, Carmen; Deschanvres, Jean-Luc
Abstract : For the first time, thin films of Vernier phase yttrium oxyfluorides, exhibiting efficient luminescence properties, are deposited on Si wafers. Abstract : In this work, we report on the first successful deposition of Vernier phase yttrium oxyfluoride (V-YOF) thin films on Si (100) wafers using pulsed liquid injection metal organic chemical vapor deposition (PLI-MOCVD). The formation of V-YOF has been confirmed by X-ray diffraction measurements and electron probe microanalysis. The infrared phonon modes of V-YOF thin films and their corresponding optical constants as inferred from spectroscopic ellipsometry are reported here for the first time. The V-YOF thin films are featured by a broad absorption band centering around 370–373 cm −1 ; their refractive index is located between those of YF3 and Y2 O3, and which shows an intimate relationship with the oxygen content in the film. The luminescence properties of Er 3+ doped V-YOF thin films are finally examined and compared with that of YF3 . Our results highlight that the as-deposited V-YOF thin films by PLI-MOCVD serve as promising candidates as efficient host material for spectral conversion for photovoltaic applications.